Investigation and management of an isolated complete distal avulsion of semitendinosus. (17th April 2018) - Ahmed, Idrees; Williams, Martin; Murray, James
Abstract : A 34-year-old male patient presented with right-sided posteromedial knee pain following an attempted tackle during a soccer match. MRI revealed that the semitendinosus (ST) tendon had completely avulsed from its distal insertion site. The patient was initially managed conservatively but eventually required surgery due to ongoing posteromedial knee pain. Surgical management was achieved through tenodesis of ST to gracilis. Postsurgery, the posteromedial knee pain had been alleviated, and following physiotherapy the patient regained a good range of motion.